Enhancing Early Childhood Development Aged 4-6 Years Through Role-Playing Method - Hafidhoh, Husnul; Fatahillah, Mubarok; El Habib, Nur (JOYCED: Journal of Early Childhood Education, 2025)
This study aims to explore the implementation of role-playing methods in enhancing various aspects of early childhood development at RA Raudhlatul Hidayah, Cirebon. A qualitative research approach was employed, utilizing data collection techniques such as observations, teacher interviews, and documentation analysis. The findings of the study indicate that role-playing significantly contributes to children's cognitive, social-emotional, language, and physical development. Children engaged in role-playing activities showed improvements in problem-solving skills, language abilities, empathy, and cooperation. However, challenges such as ensuring equal participation and the availability of resources (such as costumes and props) were identified as obstacles in the implementation of this method. Overall, the study emphasizes the importance of integrating role-playing into early childhood education curricula as a tool to support holistic child development. Recommendations for future research include examining the long-term effects of role-playing on children's development and exploring strategies to overcome implementation challenges.